2013
DOI: 10.1371/journal.pone.0078954
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Attenuates Shear-Induced Changes in Endothelial Hydraulic Conductivity by Degrading the Glycocalyx

Abstract: Diabetes mellitus is a risk factor for cardiovascular disease; however, the mechanisms through which diabetes impairs homeostasis of the vasculature have not been completely elucidated. The endothelium interacts with circulating blood through the surface glycocalyx layer, which serves as a mechanosensor/transducer of fluid shear forces leading to biomolecular responses. Atherosclerosis localizes typically in regions of low or disturbed shear stress, but in diabetics, the distribution is more diffuse, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 51 publications
(69 reference statements)
3
41
0
Order By: Relevance
“…For example, NO production and flow-dependent vasodilation of mesenteric arteries is inhibited following enzymatic degradation of the glycocalyx (393,522); a response also noted in aortic endothelial cells when the heparin sulfate content of the glycocalyx is decreased by hyperglycemia (314). There is also intriguing evidence implicating platelet-endothelial adhesion molecule-1 (PECAM-1), an endothelial cell junction molecule, as the mechanosensor.…”
Section: Intrinsic Vasoregulationmentioning
confidence: 99%
“…For example, NO production and flow-dependent vasodilation of mesenteric arteries is inhibited following enzymatic degradation of the glycocalyx (393,522); a response also noted in aortic endothelial cells when the heparin sulfate content of the glycocalyx is decreased by hyperglycemia (314). There is also intriguing evidence implicating platelet-endothelial adhesion molecule-1 (PECAM-1), an endothelial cell junction molecule, as the mechanosensor.…”
Section: Intrinsic Vasoregulationmentioning
confidence: 99%
“…The thickness of the retinal glycocalyx has been found to be significantly decreased by diabetes in a human study [199] and in a rat study, and in the latter, an increase in leukocyte adhesion was observed in the areas of markedly degraded glycocalyx [200]. In diabetes, the volume of the glycocalyx is decreased by 50% systemically, with increasing glycocalyx components in plasma [201]. In both types of diabetes, shedding of heparan sulfate (HS) chains of endothelial cells occurs due to low insulin and high glucose levels [202].…”
Section: Microvascular Damage In Drmentioning
confidence: 99%
“…In both types of diabetes, shedding of heparan sulfate (HS) chains of endothelial cells occurs due to low insulin and high glucose levels [202]. Additionally, under high glucose conditions, endothelial cells increase the rate of heparanase secretion, which leads to more HS degradation [201]. High glucose also affects the synthesis and/or metabolism of HS.…”
Section: Microvascular Damage In Drmentioning
confidence: 99%
“…Over recent years, several antibodies have been obtained against specific carbohydrate domains within HS (e.g., JM403, 10E4, and HEPSS1), HA, and CS sulfates or against the proteoglycan core proteins such as syndecan, glypican, or perlecan (31, 96 -98, 118, 119). CS and HA have been shown to be present on the endothelium, using an anti-CS antibody and by capitalizing on the proteinbinding properties of hyaluronan with a fluorescent hyaluronan binding protein (HABP), respectively (29,62,118). Although all these techniques have shown the presence of glycocalyx components on the endothelial cells, a considerable part of these studies are done using epifluorescence microscopy, which has major limitations with respect to optical spatial resolution necessary for imaging the luminal endothelial glycocalyx.…”
Section: Studying the Endothelial Glycocalyxmentioning
confidence: 99%